Physiological and Genomic Characterization of a Hyperthermophilic Archaeon Archaeoglobus neptunius sp. nov. Isolated From a Deep-Sea Hydrothermal Vent Warrants the Reclassification of the Genus Archaeoglobus - Slobodkina, Galina; Allioux, Maxime; Merkel, Alexander; Cambon-Bonavita, Marie-Anne; Alain, Karine; Jebbar, Mohamed; Slobodkin, Alexander (Frontiers in Microbiology, 2021)
Hyperthermophilic archaea of the genus Archaeoglobus are the subject of many fundamental and biotechnological researches. Despite their significance, the class Archaeoglobi is currently represented by only eight species obtained as axenic cultures and taxonomically characterized. Here, we report the isolation and characterization of a new species of Archaeoglobus from a deep-sea hydrothermal vent (Mid-Atlantic Ridge, TAG) for which the name Archaeoglobus neptunius sp. nov. is proposed. The type strain is SE56T (=DSM 110954T = VKM B-3474T). The cells of the novel isolate are motile irregular cocci growing at 50–85°C, pH 5.5-7.5 and NaCl concentrations of 1.5–4.5% (w/v). Strain SE56T grows lithoautotrophically with H2 as an electron donor, sulfite or thiosulfate as an electron acceptor and CO2/HCO3− as a carbon source. It is also capable of chemoorganotrophic growth by reduction of sulfate, sulfite or thiosulfate. The genome of the new isolate consists of a 2,115,826 bp chromosome with an overall G+C content of 46.0 mol%. The whole-genome annotation confirms the key metabolic features of the novel isolate demonstrated experimentally. Genome contains complete set of genes involved in CO2 fixation via reductive acetyl-CoA pathway, gluconeogenesis, hydrogen and fatty acids oxidation, sulfate reduction and flagellar motility. The phylogenomic reconstruction based on 122 conserved single-copy archaeal proteins supported by ANI, AAI and AF values, indicates a polyphyletic origin of the species currently included into the genus Archaeoglobus, warranting its reclassification.